Answer:
-1
Step-by-step explanation:
This all comes down to the substitution. I am assuming that (4x2) is meant to be 4x^2 so I will solve as that.
4(-2)^2 = 4(4) = 16
4(-2) = - 8
-2(3)^2 = -2(9) = -18
3(3) = 9
16-8-18+9= -1
Answer:
-2m -1
Step-by-step explanation:
(3m+5)-(6+5m)
Distribute the minus sign
(3m+5)-6-5m
Combine like terms
3m -5m +5 -6
-2m -1
Answer:
3
Step-by-step explanation:
.......................
5. 80, 16/.2=80
6. 679, 750-70.75
7. 7.82, 10-2.18
8. 36.07, 29.62+1.29+ 1.29+ 1.29+ 1.29+ 1.29